The AHR Signaling Attenuates Autoimmune Responses During the Development of Type 1 Diabetes - Yue, Tiantian; Sun, Fei; Yang, Chunliang; Wang, Faxi; Luo, Jiahui; Yang, Ping; Xiong, Fei; Zhang, Shu; Yu, Qilin; Wang, Cong-Yi (Frontiers in Immunology, 2020)
The Aryl hydrocarbon receptor (AHR) is a ligand-activated transcriptional factor widely expressed in immune cells. Its ligands range from xenobiotics and natural substances to metabolites, which renders it capable of sensing and responding to a variety of environmental cues. Although AHR signaling has long been recognized to be implicated in the pathogenesis of autoimmune disorders such as rheumatoid arthritis (RA), colitis, and systemic lupus erythematosus (SLE), its effect on the pathogenesis of type 1 diabetes (T1D), however, remains less understood. Herein in this review, we intend to summarize its potential implication in T1D pathogenesis and to sort out the related regulatory mechanisms in different types of immune cells. Emerging evidence supports that β cell destruction caused by autoimmune responses can be finely rectified by AHR signaling. Upon activation by its ligands, AHR not only modulates the development and functionality of immune cells, but also suppresses the expression of inflammatory cytokines, through which, AHR attenuates autoimmune responses during the course of T1D development. Since AHR initiated biological effect varies between different types of ligands, additional studies would be necessary to characterize or de novo synthesize effective and safe ligands aimed to replenish our arsenal in fighting autoimmune responses and β mass loss in T1D setting.